Effectiveness of the Mud Jump Training Method on Improving Volleyball Jumping Spike - Rahmat Jahri; Dicky Reva Apriana Sanga Dwi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Volleyball requires optimal jumping spike ability as the main attacking technique to score points. This skill is influenced by leg muscle strength and explosive power. This study aims to determine the effectiveness of the mud jumping training method in improving the jumping spike ability of volleyball athletes. The research employed a one group pre-test and post-test design, with a sample of 13 volleyball athletes selected purposively. The measurement instrument used was the vertical jump test. Data were analyzed using the Kolmogorov-Smirnov normality test and Paired Sample t-test with SPSS 26. The results indicated that the data were normally distributed (Sig. > 0.05) and there was a significant difference between the pre-test and post-test results (Sig. 0.000 < 0.05) with an average increase of 2.23 cm. The study concludes that the mud jumping training method is effective in improving the jumping spike ability of volleyball athletes.